What Drives Profitability of Sharia Commercial Banks? Comparison between Indonesia and Malaysia (2014-2020) - Ega Firyal Herdidewayanti; Rozmita Dewi Yuniarti; Egi Arvian Firmansyah (Universitas Pendidikan Indonesia, 2023)
Purpose - This study aims to analyze the factors affecting the profitability (proxied by profit expense ratio) of sharia commercial banks (BUS) in Indonesia and Malaysia in 2014-2020.Methodology - This study gathered secondary data from Islamic banking statistical reports published on the official website of each company. This research uses a comparative method using a quantitative approach. Sampling was carried out using the purposive sampling method, resulting in twelve banks from Indonesia and ten banks from Malaysia. The data are analyzed using panel data regression (regression pooling) in Eviews version 10 software. Findings - The results of this study show that debt financing, equity financing, and third-party funds (DPK) simultaneously affect the profitability of BUS both in Indonesia and Malaysia. Separately, debt financing and equity financing have a significant positive effect on the profitability of BUS in Indonesia, while DPK does not significantly affect it. In Malaysia BUS, debt financing, and equity financing do not affect profitability, while DPK does. This study offers a comparative analysis of profitability driven using the two ASEAN countries with the largest Muslim population, expected to contribute to Islamic banking literature.